Is thymus size at birth associated with respiratory distress syndrome in preterm infants? - Yılmaz-Semerci, Seda; Demirel, Gamze; Başkan, Özdil; Taştekin, Ayhan (IOS Press, 2019)
AIM: Thymus size in neonates depend on many factors. We aimed to assess the thymus size radiographically in preterm neonates and its relationship with respiratory distress syndrome (RDS) and other complications of prematurity. METHODS: Thymus size was assessed by cardiothymic: thoracic ratio (CT/T), measuring the width of the cardiothymic shadow at the level of carina and dividing it by the width of the thorax at the costophrenic angles, from the first chest radiograph in patients less than 34 weeks gestational age. RESULTS: Neonates born between 30-34 weeks of gestation with RDS had smaller CT/T than non RDS group (0.34±0.1 vs 0.36±0.05, p=0.045). Birth weight has positive correlation with CT/T (r=0.166, p=0.03). CONCLUSION: Thymus involution in the perinatal period is a complex process and the response is variable in different clinical situations. Activated hypothalamic-pituitary-adrenal (HPA) axis may be responsible for thymic involution in preterm infants between 30-34 weeks of gestation with RDS.
Keywords: Cardiothymic/Thoracic Ratio; Preterm Infants; Respiratory Distress Syndrome; Thymus Size